Pattern of Antimicrobial Utilization for Surgical Prophylaxis to Prevent Surgical Site Infection in Tertiary Care Teaching Hospital - S, Dudhgaonkar; MM, Bende; RS, Jagdhani; NB, Siddhawar (International Journal of Innovative Research in Medical Science, 2017)
Background: Surgical site infections (SSIs) are the second most common nosocomial infections and have adverse impact on patient. Despite proved effectiveness of surgical antimicrobial prophylaxis in reducing morbidity and mortality use is often inappropriate. However, this inappropriate use of antimicrobial agents (AMAs) leads to emergence of resistance. The objective of this study is to evaluate the pattern of surgical antimicrobial prophylaxis in our hospital to decrease SSIs and to suggest corrective measures. Material and Methods: 201 medical records of general surgery department were analysed retrospectively for five parameters of rational surgical antimicrobial prophylaxis like (i) selection (ii) timing of pre-operative dose, (iii) intra-operative dose, (iv) duration of post-operative prophylaxis and (v) unnecessary use of antimicrobial agents (AMA) were evaluated using ASHP (American Society of Health-System Pharmacists) guidelines. Results: Total 201 patients were prescribed AMA for surgical prophylaxis. The most frequent use of AMA was third generation cephalosporin and metronidazole. With regards to pre-operative dose 33.83% patients received AMAs 12 hours before surgery while no patient received intra-operative AMA. The duration of the postoperative prophylaxis extended more than 48 hours in 89.55% cases during their hospital stay. 11.94% and 35.32% cases were given unnecessary AMA in pre-operative and post-operative period respectively. 89.55% cases received AMA for long prophylaxis Conclusion: Current study revealed there is inappropriate use of AMA to prevent SSIs such as mistake in selection of AMA, excessive dosing and prolonged prophylactic use of AMA.